Perceptions of old elderly of the integral development centers for the old people - Herrera S., Fernanda (2008)
The following investigation tries to explore the field of the perception of the old ones, which they go to the centers of integral development for the old people in the municipality of Mexicali; the methodology used consisted of semi structured interviews and audio recordings, which later they were analyzed under the phenomenological perspective of the studied cases. the purpose of the same one, tries by exposing the cases, to contribute to the change of the cultural perception on such, to know external and internal the factors that affect the total development in this stage of the life, as well as, to recognize the importance that has the creation of specialized places in contributing to the bio-psico-social care of the individuals.